A TRANSLATION ANALYSIS OF FIGURATIVE LANGUAGE IN CRUELLA MOVIE - HAZIMAH LEONI; NENENG SRI WAHYUNINGSIH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
This research focused on the translation strategy used in figurative language. The aim of this research is to find out the translation strategy used in the Disney movie Cruella based on the translation strategy by Mona Baker (2018). This research used McArthur (1992) to classify the figurative language in the movie. This research is applied to the qualitative descriptive method. There are 19 data in figurative language collected by the researcher. However, there are only 17 data analyzed with four translation strategies. There is a translation by a more general word, translation by a more neutral/expressive word, translation by using related words, and translation by using unrelated words. The findings indicate that the translator applied most translation by a more general word strategy in this case, because the translator was dealing with many types of non-equivalent words in the target language.